Students' future thinking skills: Implications for school education programs - Suhendar Suhendar; Ari Widodo; Rini Solihat; Riandi Riandi (Journal of Pedagogical Research)
Future-thinking skills are crucial competencies to prepare students to face global challenges through sustainable education. However, until now there is no comprehensive profile of this skill in the context of secondary school students. This research aims to map students' future thinking skills, starting from the development and validation of multidimensional-based instruments. The five main dimensions that are the focus of the analysis include visioning and emotion, predicting, planning, anticipating, and evaluating. The instrument was developed through the stages of readability test, small-scale trial, and wide-scale validation. Rasch analysis is used to evaluate the quality of items in an instrument, while Partial Least Squares Structural Equation Modelling is applied to analyze causal relationships between dimensions. The results of the study revealed significant differences in the profile of future thinking skills based on demographic groups, such as education level and gender. In addition, the visioning and emotion dimensions were found to be key dimensions that significantly influenced other dimensions, demonstrating the importance of emotional aspects and vision in building future thinking skills. This research not only provides a map of students' future thinking skills, but also offers a robust evaluation framework based on valid and reliable instruments. The findings provide valuable insights for designing and implementing school education programs that enhance students' future-thinking competencies.